THE EFFECTS OF REFLECTIVE TEACHING ON AN INTENSIVE TEACHER TRAINING PROGRAM - Lan, Mei Hua; Kai-Ping, Wang (Universitas Pendidikan Indonesia, 2013)
Abstract: The preliminary case study was conducted to understand the effects of reflective teaching approach on English teachers' teaching performances in a short-term intensive teacher training program, and to know the participating English teachers’ feedback to the program. Totally 13 English teachers, who had taught English for 1 to 5 years, participated in this program for 3 weeks with 54 instruction hours. During the intensive program, teachers were asked to design lesson plans and demonstrate their lessons, while their peers, other experienced teachers, provided them with constructive feedback. In addition, the presenters self-assessed and reflected on their own teaching. Through several cycles of teaching demonstrations, peer-assessments, self-assessments and reflections, most teachers indicated that the reflective teaching approach was beneficial for sharpening their teaching skills, equipping them with additional teaching strategies and class management skills, and raising their awareness of the needs for examinations of their teaching reflectively in the future, and the importance of reflection of their own teaching for improvements. To give the teachers more inputs and inspirations, experienced teachers with creative teaching ideas were invited as guest speakers, and positive feedback to the guest speeches was also drawn. The findings of this study were expected to provide some pedagogical inspirations for the related fields, especially English teacher training in EFL contexts.